2006
DOI: 10.1002/sita.200500062
|View full text |Cite
|
Sign up to set email alerts
|

Blimp‐1 is expressed in human and mouse T cell subsets and leads to loss of IL‐2 production and to defective proliferation

Abstract: The transcriptional repressor Blimp-1 regulates terminal differentiation of B-lymphocytes and myeloid cells. We now show that Blimp-1 is also expressed in human and murine primary T lymphocytes. Blimp-1 expression is highest in freshly isolated primary T cells with an antigen experienced phenotype. Th2 and CD4 + CD25 + cells exhibited higher levels of Blimp-1 mRNA than Th1 cells. However, ectopic expression of Blimp-1 by retroviral transduction neither altered the frequency of IFN-c or IL-4 producing cells nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
4
10
0
Order By: Relevance
“…In this model, the terminal differentiation of effector CD8 + T cells requires both Blimp-1 and a parallel, inflammatory, pathway that supports high T-bet expression (Joshi et al, 2007). This latter possibility is in line with the finding that Prdm1 expression in activated T cells is regulated by IL-2 Gong and Malek, 2007;Santer-Nanan et al, 2006) and that memory T cells generated in the absence of IL-2 signaling are, similar to Blimp-1-deficient memory cells, functionally impaired in their ability to differentiate into effector cells (Williams et al, 2006). Thus our data directly implicate Blimp-1 in the ''programming'' of memory T cells.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this model, the terminal differentiation of effector CD8 + T cells requires both Blimp-1 and a parallel, inflammatory, pathway that supports high T-bet expression (Joshi et al, 2007). This latter possibility is in line with the finding that Prdm1 expression in activated T cells is regulated by IL-2 Gong and Malek, 2007;Santer-Nanan et al, 2006) and that memory T cells generated in the absence of IL-2 signaling are, similar to Blimp-1-deficient memory cells, functionally impaired in their ability to differentiate into effector cells (Williams et al, 2006). Thus our data directly implicate Blimp-1 in the ''programming'' of memory T cells.…”
Section: Discussionsupporting
confidence: 75%
“…Mice with a T cell-specific deletion of Blimp-1 or mice reconstituted with Blimp-1-deficient fetal liver cells show a pronounced accumulation of antigen-experienced T cells and develop severe T cell-mediated immune pathology (Kallies et al, 2006;Martins et al, 2006). Subsequent studies revealed that Blimp-1 is induced by IL-2 and represses Il2 transcription in a negative feedback loop Gong and Malek, 2007;Santer-Nanan et al, 2006). The function of Blimp-1 in T cell differentiation and its role in T cell responses in vivo, however, have not been addressed.…”
Section: Introductionmentioning
confidence: 95%
“…Members of the NFAT family of transcriptional factors associate with different partners to regulate key aspects of T-helper-cell differentiation (47). In T lymphocytes, Prdm1 expression is induced by inflammatory cytokines and in response to receptor signaling (20,28,49,70). Prdm1 regulates T-cell proliferation, survival, homeostasis, and terminal differentiation (28,49).…”
Section: Discussionmentioning
confidence: 99%
“…Both IL-12 and IL-4 have been shown to induce Blimp-1, but IL-4 seems to be a stronger Blimp-1 inducer cytokine than IL-12 (20). In agreement, Blimp-1 expression level in Th1 CD4 T cells is lower in Th2 CD4 T cells (40). IL-27 is another cytokine that limits IL-2 production by CD4 T cells (30).…”
Section: Discussionmentioning
confidence: 66%
“…Bcl-6 mRNA was found elevated in Blimp-1 -deficient T cells (17). As Bcl-6 inhibits GATA-3 expression and represses Th2 differentiation (39) and T-bet promotes Th1 differentiation, Blimp-1 might be a transcription factor highly associated with Th2 differentiation that cooperates with GATA-3 (40). Indeed, elevation in IFN-␥ production and Th1-mediated pathology observed in Blimp-1-deficient animal models supports this notion (18,19).…”
Section: Discussionmentioning
confidence: 80%